2010
DOI: 10.1016/j.econlet.2010.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Behavior under social pressure: Empty Italian stadiums and referee bias

Abstract: This paper studies how social pressure affects the behavior of soccer referees. We make use of an attractive source of exogenous variation in the number of spectators at matches. Due to recent hooligan violence, the Italian government has implemented a regulation that forces some soccer teams to temporarily play home matches in empty stadiums. We find that referees punish away players more harshly and home players more lightly when the games are played in front of spectators compared to when they are not. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
92
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 11 publications
9
92
1
2
Order By: Relevance
“…There currently exists no consensus over which mechanism is the most important, with some researchers arguing for the impact on players (Agnew & Carron, 1994;Bray & Widmeyer, 2000) and others suggesting a referee bias (Dohmen, 2008;Garicano et al, 2005;Pettersson-Lidbom & Priks, 2007;Sutter & Kocher, 2004). Both mechanisms are plausible and it is likely that each contribute to the overall home advantage.…”
Section: Introductionmentioning
confidence: 92%
“…There currently exists no consensus over which mechanism is the most important, with some researchers arguing for the impact on players (Agnew & Carron, 1994;Bray & Widmeyer, 2000) and others suggesting a referee bias (Dohmen, 2008;Garicano et al, 2005;Pettersson-Lidbom & Priks, 2007;Sutter & Kocher, 2004). Both mechanisms are plausible and it is likely that each contribute to the overall home advantage.…”
Section: Introductionmentioning
confidence: 92%
“…A pesar de ello, las tendencias indican que los árbitros principales de 1ª División presentan un mayor riesgo de sufrir el síndrome. Estos resultados son acordes con otros estudios en torno a diferentes estresores (Louvet, et al, 2009;Pettersson-Lidbom & Priks, 2010).…”
Section: Discusión Y Conclusionesunclassified
“…En este sentido, diversos trabajos han confirmado cómo diversas variables como la percepción subjetiva del juego, la presión ejercida por el público, los jugadores y los propios entrenadores o el efecto de diferentes estresores relacionados con el entorno más próximo al árbitro ejercen un efecto directo sobre su bienestar emocional (Debien, Noce, Debien, & Costa, 2014;Louvet, et al, 2009;Pettersson-Lidbom & Priks, 2010).…”
Section: Introductionunclassified
“…This is not just supported by the prevalence of beneficial calls in favor of the home team, but also by the findings about the influence of different crowd settings. Pettersson-Lidbom and Priks (2010), as an example, showed that referees did not favor the home team in the same way when spectators were excluded. Similar to other real life settings, like economy or education, another source of bias are race, origin and ethnicity.…”
Section: Introductionmentioning
confidence: 99%